A significant enhancement of color transition from an on–off type achromatic colorimetric nanosensor for highly sensitive multi-analyte detection with the naked eye. Issue 43 (20th October 2016) - Heo, Jun Hyuk; Yi, Gyu Sung; Lee, Byoung Sang; Cho, Hui Hun; Lee, Jin Woong; Lee, Jung Heon
Abstract : We report an on–off type achromatic nanoparticle-based colorimetric sensor with significantly enhanced color transition and increased sensitivity for naked-eye inspection. Abstract : Here, we report the development of an achromatic nanoparticle-based colorimetric sensor (achromatic nanosensor) with an on–off type color change that significantly enhances the color transition and increases the sensitivity of the sensor for naked-eye inspection. The achromatic nanosensor was prepared via a modified CMYK (CRYK) subtractive color model by combining DNA-functionalized gold nanoparticles (AuNPs-DNA), silver nanoparticles (AgNPs-DNA), and gold nanorods (AuNRs-DNA). The initially black-colored achromatic nanosensor not only allowed multiplexed detection by generating target-specific diverse color changes, but also improved the recognition of color changes by the naked eye. Thus, this on–off type color change enabled analysis near the limit of detection (LOD) with the naked eye. In addition, we developed a new image processing method adapted for this achromatic sensor. By quantifying the saturation value of the color images of the achromatic sensor, we could significantly amplify the color signal of the samples, which is difficult to achieve with general colorimetric sensors. The practical application of this achromatic nanosensor for biomarker detection was demonstrated with thrombin and platelet-derived growth factor (PDGF) in human blood plasma. These results provide a new sensing platform that is applicable to most NP-based colorimetric sensing systems for a wide range of applications, including biomolecular diagnosis, chemical pollutant sensing, environmental monitoring, etc .